Hubungan Pengetahuan, Sikap Dan Dukungan Keluarga Dengan Risiko Penularan TB Paru - Daniel Ginting; Nina Fentiana (Jurnal Ilmu Kesehatan dan Gizi, 2023)
In 2019 the total number of tuberculosis cases in North Sumatra was recorded at 99,398 cases, while in 2020 there were 78,698 cases and in 2021 there were 57,247 cases. This study aims to look at the relationship between knowledge, attitudes and family support with the risk of pulmonary TB transmission. This type of research is survey research which is analytic in nature. Cross sectional research design. The sample is pulmonary TB patients in the Working Area of the Kartini Public Health Center, Pematang Siantar City for the period of October 2022 as many as 44 people. Data analysis using chi square. The results of the study concluded that there is a relationship between knowledge, attitudes and family support with the risk of pulmonary TB transmission in the family. The role of health workers and Community Health Centers is as a source of correct information through applicative counseling by giving leaflets to pulmonary TB patients.